2016
DOI: 10.1097/ccm.0000000000001561
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Properties of Argon After Experimental Subarachnoid Hemorrhage: Early Treatment Reduces Mortality and Influences Hippocampal Protein Expression*

Abstract: Argon application after experimental subarachnoid hemorrhage met the primary endpoint of reducing the risk of mortality. In addition, higher body weight indicating good overall condition was observed in the argon group over the entire observation period. Regarding the mechanism of action, hypoxia-inducible factor 1α-induced heme oxygenase 1 expression resulting in improved survival of neurons may contribute to the beneficial effect of argon application after subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
4
33
0
1
Order By: Relevance
“…In the initial trial design, a 24-h clinical evaluation using an 18- and 28-point scoring system was included. After the negative results in a similar study with argon, where we observed no difference in neurologic function in the acute phase ( 26 ), no short-term neurological evaluation was done in this trial.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the initial trial design, a 24-h clinical evaluation using an 18- and 28-point scoring system was included. After the negative results in a similar study with argon, where we observed no difference in neurologic function in the acute phase ( 26 ), no short-term neurological evaluation was done in this trial.…”
Section: Methodsmentioning
confidence: 84%
“…SAH was induced by the polypropylene monofilament perforation technique initially described by Bederson et al and modified by Veelken et al ( 24 , 25 ). The procedure was performed as previously described ( 26 ). After exposing the left common carotid artery, the left internal carotid artery (ICA) was identified and a 3–0 polypropylene suture with a diameter ranging from 200 to 250 µm (Prolene suture, Ethicon Inc., Somerville, NJ, USA) was advanced intravascularly.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the reported functional and histopathological neuroprotective effect in other traumatic, hypoxic and ischemic brain injury models has also been demonstrated in normothermic conditions 112627282930. A neuroprotective effect of noble gases can therefore not be explained by an augmented protective effect of hypothermia alone.…”
Section: Discussionmentioning
confidence: 92%
“…Höllig et al [28] recently published the results of a new model, inducing brain injury by subarachnoid hemorrhage in rats. One hour after an intracranial endovascular perforation procedure, animals received argon 50% (50% O 2 ).…”
Section: Argon As a Neuroprotective Gaseous Molecule In Various Momentioning
confidence: 99%
“…After induction of subarachnoid hemorrhage (SAH) in rats, Höllig et al [28] performed Western blot analysis for HO-1 and HIF-1α protein of hippocampal tissue at different time points. The results are difficult to interpret; while argon treatment reduced HO-1 protein expression at 6 h after SAH, HO-1 was ultimately induced at 24 h. Furthermore, HIF-1α protein expression was significantly increased only after 24 h due to argon inhalation, while both proteins failed to show any elevated expressions at 72 h post injury.…”
Section: Intracellular Pathways Displaying Argon-mediated Neuropromentioning
confidence: 99%